2018
DOI: 10.1002/fsn3.604
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient, phytochemical, and antinutrient composition of Citrus maxima fruit juice and peel extract

Abstract: Nutrient, phytochemical, and antinutrient composition of Citrus maxima fruit juice and peel extract were determined. The fruit was procured from a garden in Trans‐Ekulu, Enugu East Local Government Area, Enugu State, Nigeria. Mature undamaged Citrus maxima fruits were thoroughly washed with distilled water to remove contamination, dirt, and air‐dried. The peel was separated from the pulp. The pulp (100 g) was blended and filtered through a muslin cloth to obtain a clear juice. The peel (50 g) was macerated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 24 publications
6
30
4
2
Order By: Relevance
“…The anti-diabetic potential of Citrus maxima peel extract is associated with its wealth of phytochemicals. Earlier phytochemical analysis of Citrus maxima peel extract sourced from the same location as that used in the present study revealed high amount of alkaloid (3498.37 mg/100 g), phenolics (1799.07 mg/100 g), flavonoids (1511.74 mg/100 g) and saponin (24.51 mg/100 g) (Ani and Abel, 2018). Phytochemicals are bioactive non-nutrient plant compounds that have been proven to reduce the risk of developing chronic diseases such as diabetes.…”
Section: Anti-diabetic Potential Of Citrus Maxima Peel Extractsupporting
confidence: 53%
See 2 more Smart Citations
“…The anti-diabetic potential of Citrus maxima peel extract is associated with its wealth of phytochemicals. Earlier phytochemical analysis of Citrus maxima peel extract sourced from the same location as that used in the present study revealed high amount of alkaloid (3498.37 mg/100 g), phenolics (1799.07 mg/100 g), flavonoids (1511.74 mg/100 g) and saponin (24.51 mg/100 g) (Ani and Abel, 2018). Phytochemicals are bioactive non-nutrient plant compounds that have been proven to reduce the risk of developing chronic diseases such as diabetes.…”
Section: Anti-diabetic Potential Of Citrus Maxima Peel Extractsupporting
confidence: 53%
“…Antioxidants play important roles in inhibiting both free radicals and oxidative chain reactions within the tissues and cell membranes. Earlier study (Ani and Abel, 2018) reported a significant amount of antioxidant vitamins E and C in Citrus maxima peel extract. In addition to phytochemicals, the antidiabetic effect of Citrus maxima peel extract observed in the present study could be attributed to the antioxidant vitamins.…”
Section: Anti-diabetic Potential Of Citrus Maxima Peel Extractmentioning
confidence: 90%
See 1 more Smart Citation
“…The industry uses very little of the waste for the production of pectin, molasses, fibers, oils [11], and animal food [12]. Nevertheless, these by-products contain high levels of vitamin C [13], thiamine, niacin, pyridoxine, phosphorus, calcium, iron, magnesium, and potassium [14], as well as soluble and insoluble dietary fibers [15]. Fruit residues are also sources of bioactive compounds, especially flavonoids and phenolic acids [16].…”
Section: Introductionmentioning
confidence: 99%
“…Peel of the citrus fruits is considered to be rich in polyphenols than the inner edible portion of fruit. These polyphenols may possess antioxidant, anticancer, antiviral, and anti‐inflammatory properties which can be utilized to develop functional foods (Ani & Abel, ). Citrus peel is rich in dietary fiber and ratio of soluble and insoluble dietary is higher compared to the cereals (Chau & Huang, ).…”
Section: Introductionmentioning
confidence: 99%